Cloning and Expression of Small Hepatitis B Surface Antigen (sHBsAg) In Hansenula polymorpha (Indonesian Society for microbiology, 2016)
Recombinant small hepatitis B surface antigen (sHBsAg) is used as a vaccine component to prevent hepatitis B virus infection. As an attempt to produce local recombinant sHBsAg, a PCR-amplified DNA fragment encoding Indonesia sHBsAg which belongs to B genotype and adw2 subtype was cloned into Hansenula polymorpha expression vector pHIPX4 by using recombination method. The resulted pHIPX4-sHBsAg was integrated into the alcohol oxidase (AOX) locus of H. polymorpha NCYC495 genome and the sHBsAg expression was regulated under the control of H. polymorpha AOX promoter. H. polymorpha NCYC495 carrying the sHBsAg coding sequence was grown in mineral medium and methanol 0.5% (v/v) was added to induce the expression of recombinant sHBsAg. The expression of sHBsAg was detected by HBsAg diagnostic kit test, ELISA, and Western blot analysis.